Farmakoantartika Literature Study: Bioactivity of Pagodroma nivea on Fossil Deposits from Mujito - Saristiana, Yuneka; Prasetyawan, Fendy; Mildawati, Ratna; Muslikh, Faisal Akhmal; Dhafin, Anis Akhwan; Raharjo, Susilo Margining; Arifin, Candra; Rofiq, Abd (PT FORMOSA CENDEKIA GLOBAL, 2023)
This report investigates the biodiversity of marine animals, focusing on extinct sponge species near Lesbos Island based on Aristotle's descriptions. Mujito, introduced in the literature review, is from the GeoMaud expedition in Antarctica. Various instrumental analysis methods, such as ESI mass spectrometry and NMR, contribute to a comprehensive understanding of the compounds, particularly in the context of Alzheimer's research. The pharmacantarctic literature study concludes that Antarctic Mumijo, particularly from Mujito fossil deposits, holds significant biomedical potential. It exhibits organic components like wax esters with notable biomedical activities, particularly in treating bone diseases. Additionally, Mumijo's composition resembles non-fossil samples, with wax esters dominating and unique components like α-glyceryl fatty alcohol ethers indicating neuroprotective potential. The research suggests promising applications in Oriental medicine, addressing wounds, skin diseases, tuberculosis, respiratory diseases, and neurological conditions like Parkinson's and Alzheimer's. Overall, Antarctic Mumijo showcases diverse biomedical prospects, emphasizing its organic components' therapeutic value